Si Jose at si Bonifacio [videorecording] - Jacob, Malou; Santos, Libertine C.; Sentrong Pangkultura ng Pilipinas (Manila Sentrong Pangkultura ng Pilipinas, 1996)
A documentary film on the life and times of Jose Rizal and Andres Bonifacio.
VHS.
Narrator, Joonee Gamboa.
Keywords: Rizal, Jose -- 1861-1896.; Bonifacio, Andres -- 1863-1897.